BCL10-CARD11 Fusion Mimics an Active CARD11 Seed That Triggers Constitutive BCL10 Oligomerization and Lymphocyte Activation - Seeholzer, Thomas; Kurz, Susanne; Schlauderer, Florian; Woods, Simone; Gehring, Torben; Widmann, Simon; Lammens, Katja; Krappmann, Daniel (Frontiers in Immunology, 2018)
Assembly of the CARD11/CARMA1-BCL10-MALT1 (CBM) signaling complex upon T or B cell antigen receptor (TCR or BCR) engagement drives lymphocyte activation. Recruitment of pre-assembled BCL10-MALT1 complexes to CARD11 fosters activation of the MALT1 protease and canonical NF-B signaling. Structural data and in vitro assays have suggested that CARD11 acts as a seed that nucleates the assembly of BCL10 filaments, but the relevance of these findings for CBM complex assembly in cell remains unresolved. To uncouple cellular CARD11 recruitment of BCL10 and BCL10 filament assembly, we generated a BCL10-CARD11 fusion protein that links the C-terminus of BCL10 to the N-terminus of CARD11. When stably expressed in CARD11 KO Jurkat T cells, the BCL10-CARD11 fusion induced constitutive MALT1 activation. Furthermore, in CARD11 KO BJAB B cells, BCL10-CARD11 promoted constitutive NF-B activation to a similar extent as CARD11 containing oncogenic driver mutations. Using structure-guided destructive mutations in the CARD11-BCL10 (CARD11 R35A) or BCL10-BCL10 (BCL10 R42E) interfaces, we demonstrate that chronic activation by the BCL10-CARD11 fusion protein was independent of the CARD11 CARD. However, activation strictly relied upon the ability of the BCL10 CARD to form oligomers. Thus, by combining distinct CARD mutations in the context of constitutively active BCL10-CARD11 fusion proteins, we provide evidence that BCL10-MALT1 recruitment to CARD11 and BCL10 filament formation are interconnected processes, which bridge the CARD11 seed to downstream pathways in lymphocytes.